Job Analysis Using The DACUM Method An Applied Study Of The Opinions Of A Sample Of Department Heads In The Colleges Of The University Of Babylon - Maysoon Ali Hussein; Reem Qasim Hassan; Mohammed sadeq Mohammed Ali (Academia Open, 2025)
General Background: Human resource management increasingly depends on accurate job analysis to ensure the optimal allocation of duties, qualifications, and organizational structures. Specific Background: The DACUM (Design a Curriculum) methodology has gained prominence as a competency-based approach that systematically identifies duties and tasks directly from job holders, allowing alignment between actual job content and institutional expectations. Knowledge Gap: Despite its advantages, limited empirical evidence exists on the effectiveness of DACUM for academic administrative roles in Middle Eastern higher education, particularly regarding its capacity to reduce discrepancies between job descriptions and real job practices. Aims: This study investigates the degree of DACUM application among department heads at the University of Babylon and examines its role in improving job analysis, job descriptions, and organizational clarity. Results: Quantitative analysis of 25 valid questionnaires revealed high response intensities across DACUM components, with an overall mean score of 3.69, indicating strong perceived relevance. Several items achieved response strengths exceeding 90%, demonstrating broad agreement that DACUM enhances alignment between duties, competencies, and administrative needs. Novelty: The study provides empirical validation of DACUM within an academic administrative context, offering a structured model that integrates theory, practice, and local organizational requirements. Implications: Findings highlight the value of adopting DACUM to reduce role ambiguity, refine training needs, improve performance evaluation systems, and strengthen the linkage between organizational structures and labor-market expectations within higher education institutions.Highlight : DACUM clarifies duties, responsibilities, and competencies for more accurate job analysis. Employees serve as the primary source for describing actual job content. DACUM aligns job analysis with training needs in a relevant way. Keywords : DACUM Mechanism, Job Analysis, Heads of Scientific Departments, Organizational Structure, Training Programs